More than a babysitter: Looking back on an effective summer enrichment program - Benterah Morton; Kelly Byrd; Elizabeth Allison; Andre Green (Arizona State University, 2021)
Each summer families across the globe send their children to summer camps and daycares for what amounts to babysitting. This study takes the discussion beyond babysitting and explores a unique summer enrichment program offered to rising second through fifth grade students in a modified enrichment camp model. During the four-week program, students were engaged in standards-based academic instruction in reading, mathematics, and science designed to provide enrichment activities to better prepare them for academic success in the upcoming year. Students were pre-tested over standards from the first quarter of the upcoming year. Then, they were taught the standards and post-tested. Analysis of the pretest and posttest data suggests that the program was successful in increasing students' content knowledge in each of the subject areas taught. The findings imply that summer programs intentionally offering standards-based academics in an enrichment camp environment can be used to provide learning opportunities that diminish academic opportunity gaps.